Hypokalemic paralysis in an adolescent following dexamethasone and B12 injection: A case report and literature review - Keivan Sahebi; Hassan Foroozand; Mohammad Bahmei; Raziee Taghizadeh; Samane Zare; Soroor Inaloo (Heliyon)
The widespread use of glucocorticoids in clinical practice may occasionally be complicated by hypokalemic paralysis. Previously, only a few cases of glucocorticoid-induced hypokalemic paralysis in healthy adults had been reported. Intriguingly, cases of B12-induced hypokalemia have previously been reported in patients with pernicious anemia. Recently, we experienced a case of hypokalemic paralysis in an adolescent following intramuscular injections of dexamethasone and vitamin B12. Upon exclusion of other causes, a presumptive diagnosis of glucocorticoid-induced hypokalemic paralysis, with a possible but uncertain contribution from B12 supplementation, was made for the patient. After potassium replacement therapy, the patient fully recovered and was discharged after five days. Although glucocorticoids are known to cause hypokalemia through mechanisms such as enhanced transcellular shift or renal excretion, the potential role of vitamin B12 in worsening this effect remains unclear. It is hypothesized that B12 supplementation under certain conditions could influence electrolyte balance and potentially amplify the hypokalemic effects of glucocorticoids. However, this hypothesis is based on a few cases, and further pathophysiological and clinical studies are needed to clarify whether B12 supplementation exacerbates hypokalemia induced by glucocorticoids or if the observation is coincidental or context-specific. Meanwhile, clinicians should be cautious when prescribing glucocorticoids, particularly in combination with B12 supplements. This includes ensuring that both are administered only when clinically indicated, monitoring vital signs and serum potassium levels in at-risk patients, and considering alternatives when appropriate.